2007
DOI: 10.1016/j.dnarep.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of cell cycle delay following targeted gene repair by oligonucleotides

Abstract: We have previously shown that activation of the homologous recombinational repair pathway leads to a block of cell division in corrected cells, possibly through the activity of checkpoint proteins Chk1 and Chk2. In this study, we examine the long term impact of this stalling on the growth of cells that have enabled gene repair events. Using a mutated eGFP gene as an episomal reporter, we show that corrected (eGFP positive) cells contain only a few active replication templates two weeks after electroporation, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…4B and suggest an ODN-independent single-strand break activity since the control (No ODN) exhibits the same pattern described above. However, it is pertinent to consider that cells treated with ODN experience a significant delay in replication; a process that can generate transient single-stranded breaks [13, 16, 18, 34, 35]. Therefore, the demonstrated lag in replication in ODN-treated cells, as seen with both the BrdU incorporation assay (Figure 4C) and cell counts after recovery (data not shown), implicate that ODN treatment is responsible for some degree of single-stranded break occurrence independent of normal cellular replication.…”
Section: Resultsmentioning
confidence: 99%
“…4B and suggest an ODN-independent single-strand break activity since the control (No ODN) exhibits the same pattern described above. However, it is pertinent to consider that cells treated with ODN experience a significant delay in replication; a process that can generate transient single-stranded breaks [13, 16, 18, 34, 35]. Therefore, the demonstrated lag in replication in ODN-treated cells, as seen with both the BrdU incorporation assay (Figure 4C) and cell counts after recovery (data not shown), implicate that ODN treatment is responsible for some degree of single-stranded break occurrence independent of normal cellular replication.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these problems were best characterized by Olsen et al 12 First, as reported by many labs, 17,21,22 little correction activity occurs in the G1 phase of the cell cycle. Second, it is now clear that proteins involved in homologous recombination participate in TGA because transcription itself enhances homologous recombination.…”
Section: Targeted Gene Alteration H Parekh-olmedo and Eb Kmiecmentioning
confidence: 99%
“…This issue was examined in greater detail however, and it was found that corrected cells regain replicative activity fully. 22 During this lag period, the non-corrected cells advance through several rounds of replication and cell divisions initially 'outgrowing' the corrected population. As a result the correction frequency appears to diminish until the replication potential of corrected cells is restored.…”
Section: Targeted Gene Alteration H Parekh-olmedo and Eb Kmiecmentioning
confidence: 99%
“…The frequency with which these events occur is highly dependent on the introduction of a large amount of ssODN into the target cell, a type of mass action effect45. The frequency of the process, known as gene editing, can be enhanced by the pre-treatment with reagents or drugs that induce double strand (ds) DNA breakage678.…”
mentioning
confidence: 99%